Understanding the trends of maternal mental health research in India through bibliometric analysis - Singh, Alok; Verma, Diksha (International Journal Of Community Medicine And Public Health, 2023)
Pregnancy-related mental health issues are more common in low and middle‐income countries (LMICs). Common mental health disorders are more prevalent among women than men. In LMIC countries, the prevalence of mental health disorders is higher, estimated at 15.6% among pregnant women and 19.8% among postpartum women. According to the studies, Antenatal depression prevalence in India ranged from 9.8% to 36.7%, while antenatal anxiety prevalence was 55.7%. This study performed bibliometric profiling to shed light on maternal mental health research conducted in India since 1979 and to present the research output in the field of maternal mental health in India. SCOPUS databases have been chosen for data retrieval due to their extensive coverage, high-impact journal inclusion and ease of access to quality publications. In total, 146 publications were found in the field. Maternal mental health research increased significantly in 2022. The peak number of publications occurred in 2022.There has been a lot of focus on maternal mental health. This is evidenced by the fact that there has been a significant increase in the number of scientific publications in India since 1979. The bibliometric indicators provided important information on the research contributions from different institutes and authors. The results of this study can serve as a reference for researchers and policymakers to plan future research.